Nanoparticles: Characteristics, Preparation, Applications and Challenges in Modern Technologies - Kasimedu, Saravanakumar; Selvam, Usha Priya Halapaka; Sharma, Keerthishree Suresh; Arrivur, Navina Sreenivasan; Pommala, Nagaveni; Mudduluru, Niranjan Babu; Gandla, Mallikarjuna; Vadamala, Prudhvi Raj (Pharmaceutical Science: New Insights and Developments Vol. 3, 2025)
Nanoparticles have distinctive characteristics such as their particle size ranges from 1-1000 nm and exhibit special physical, chemical and biological properties and have become a future-proof technology. It has broad effects on a number of sectors including consumer goods, energy and medicine. This overview offers a thorough analysis of the many kinds of nanoparticles, such as polymeric nanoparticles, solid lipid nanoparticles, metallic nanoparticles, etc., as well as methods for preparing and assessing them. The advantages of nanoparticles include increased solubility, targeted drug delivery, enhanced bioavailability and many more. There are many applications of nanoparticles in many fields such as diagnostics, therapeutics, imaging and biosensing. However, there are even demerits of these as potential toxicity, immunogenicity, environmental impacts and even cost is also pretty high. Some of the demerits can be overcome by careful assessment of the manufacturing technique. Furthermore, necessary evaluation techniques can be considered for characterizing the size, shape, surface area and other significant characteristics of nanoparticles.